Post-NPM and re-centralisation: current themes in Europe and Turkey. Issue 2 (3rd April 2018) - Demir, Fatih
ABSTRACT: Since 1980s, European Union countries have witnessed significant transformations as regards public management reforms. This era can be examined in two periods. Until mid-1990s the reforms were heavily influenced by the principles of new public management (NPM) paradigm whereas the second period of reforms was handled in the midst of intense criticism towards NPM. Today debate on public management reforms is omnipresent in the entire European Union. On the other hand, the EU requests candidate countries to put into practice public management reforms. The potential effectiveness of such demands is far from being clear in an environment where intense debates are ongoing over the path that public management reforms should take. Some studies show that there is increasing confusion on the direction of public management reforms especially after the 2008 economic crisis. In Turkey, reactionary measures were taken against NPM regulations which led to the fragmentation of central authority: independent regulatory agencies were put under tighter control of the government, and prime minister's office and president's office were expanded and reinforced. A closer look at these practices implicates that these steps are beyond fashioning an integrated administration as a response to the fragmentation in the central government.